Energy balance and macronutrient intake during season trainings: influence on anthropometric and lipid profiles in professional athletes - Marcia Godoy Gowdak; Luciene Ferreira Azevedo; Patricia Perlingeiro; Luciana Diniz Nagem Janot De Matos (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2017)
This study evaluated energetic balance and macronutrient intake at competitive training and transition training and their impact on anthropometric and lipid profiles in sixteen professional male athletes. Dietary data, body composition measurements and lipid profile were obtained at the end of both season trainings. Despite increased carbohydrate supplementation during exercise and higher caloric intake at competitive training (+10%, P =0.01), total daily energy expenditure was higher than caloric intake (79%, P<0.001). These results show negative energy balance at competitive training. However, total daily energy expenditure and caloric intake were similar at transition training (P =0.35). Higher intake of carbohydrate, fat, and protein were observed at competitive training (+13%, P =0.001 for all), although caloric intake was below the requirements during this period. Body mass (+2%, P =0.05), body fat percentage (+56%, P =0.01), fat mass (+57%, P =0.01), and waist and hip circumferences (+10%, P =0.004) were higher at transition training, as well as total and LDL-cholesterols (+14%, P =0.001). Endurance athletes showed negative energy balance at competitive training and maintained similar caloric intake at transition training despite decreased total daily energy expenditure, which might have contributed to changes in anthropometric and lipid profiles. These findings emphasize the importance of nutritional counseling for professional athletes during different season trainings.   RESUMO  Balanço energético e ingestão de macronutrientes  durante periodos de treinamento: influência nos perfis antropométrico e lipídico em atletas profissionais Este estudo avaliou o balanço energético e a ingestão de macronutrientes nos treinamentos competitivo e de transição do treinamento e o seu impacto nos perfis antropométrico e lipídico de dezesseis atletas profissionais. Dados da dieta, medidas da composição corporal e perfil lipídico foram obtidos no final de ambos os treinamentos físico. Apesar do aumento da suplementação de carboidrato durante exercício e maior ingestão calórica no treinamento competitivo (+10%, P =0,01), o gasto energético diário total foi maior do que a ingestão calórica (79%, P<0,001), mostrando balanço energético negativo no treinamento competitivo. Entretanto, o gasto energético diário total e ingestão colórica foram similares no treinamento de transição (P =0,35). Maior ingestão de carboidrato, lipídio e proteína foram observados no treinamento competitivo (+13%, P =0,001), embora a ingestão calórica tenha sido abaixo da recomendada. Massa corporal (+2%, P =0,05), percentual de gordura corporal (+56%, P =0,01), massa de gordura (+57%, P =0,01), e circunferências de cintura e quadril (+10%, P =0,004) foram maiores no treinamento de transição, assim como o cholesterol total e LDL-c (+14%, P =0,001). Atletas de resistência apresentaram balanço energético negativo no treinamento competitivo e mantiveram ingestão calórica similar no treinamento de transição, apesar da diminuição do gasto energético, o que provavelmente contribuiu para as mudanças nos perfis antropométrico e lipídico. Esses achados ressaltam a importância do aconselhamento nutricional para atletas nos diferentes períodos do treinamento.